A Singlet Oxygen Photogeneration and Luminescence Study of Unsymmetrically Substituted Mesoporphyrinic Compounds. (26th April 2009) - Oliveira, Anabela Sousa; Licsandru, Dumitru; Boscencu, Rica; Socoteanu, Radu; Nacea, Veronica; Vieira Ferreira, Luis Filipe
Abstract : This paper deals with a series of new unsymmetrically substituted mesoporphyrins: 5-(2-hydroxyphenyl)-10, 15, 20-tris-phenyl-21, 23-H-porphyrin (TPPOH O ), 5-(3-hydroxyphenyl)-10, 15, 20-tris-phenyl-21, 23-H-porphyrin (TPPOH M ), 5-(4-hydroxyphenyl)-10, 15, 20-tris-phenyl-21, 23-H-porphyrin (TPPOH P ), 5-(2-hydroxyphenyl)-10, 15, 20-tris-butyl-21, 23-H-porphyrin (TBPOH O ), and their parent nonsubstituted compounds, respectively, 5, 10, 15, 20-tetrakis-phenyl-21, 23-H-porphyrin (TPP) and 5, 10, 15, 20-tetrakis-butyl-21, 23-H-porphyrin (TBP). Several photophysical studies were carried out to access the influence of the unsymmetrical substitution at the porphyrinic macrocycle on porthyrin's photophysical properties, especially porthyrin's efficiency as singlet oxygen sensitizers. The quantum yields of singlet oxygen generation were determined in benzene (Φ Δ (TPP) = 0.66 ± 0.05;Φ Δ (TPPOH O ) = 0.69 ± 0.04;Φ Δ (TPPOH M ) = 0.62 ± 0.04;Φ Δ (TPPOH P ) = 0.73 ± 0.03;Φ Δ (TBP) = 0.76 ± 0.03;Φ Δ (TBPOH O ) = 0.73 ± 0.02) using the 5, 10, 15, 20-tetraphenyl-21, 23-H-porphine (Φ Δ (TPP) = 0.66) and Phenazine (Φ Δ (Phz) = 0.83) as reference compounds. Their fluorescence quantum yields were found to be (Φ f (TPPOH O ) = 0.10 ± 0.04;Φ f (TPPOH M ) = 0.09 ± 0.03;Φ f (TPPOH P ) = 0.13 ± 0.02;Φ f (TBP) = 0.08 ± 0.03 andΦ f (TBPOH O ) = 0.08 ± 0.02 using 5, 10, 15, 20-tetraphenyl-21, 23-H-porphine as referenceΦ f (TPP) = 0.13). Singlet state lifetimes were also determined in the same solvent. All the porphyrins presented very similar fluorescence lifetimes (mean values ofτ S (withO 2, air equilibrated) = 9.6 ± 0.3 nanoseconds and (withoutO 2, argon purged) = 10.1 ± 0.6 nanoseconds, resp.). The phosphorescence emission was found to be negligible for this series of unsymmetrically substituted mesoporphyrins, but an E-type, thermally activated, delayed fluorescence process was proved to occur at room temperature.